Percepção sensorial tátil prejudicada: identificação do fenômeno em grupos predisponentes - Morais, Huana Carolina Cândido (2016)
Impaired tactile sensory perception is defined as change or inability to interpret stimuli provided under ideal conditions that come into contact with the body surface of the individual, due to changes in superficial and deep skin tactile receptors in nerve fibers conduction or cerebral interpretation of there. It is verified that the tactile sensory changes are referred to, but the evaluation of their presence is harmed by a lack of rigorous methodological procedures which are common to all predisposing conditions to alterations. It is recognized that nurses need to take into account the sensory changes in the planning of care. The aim of the study was to clinically characterize the tactile sensory perception phenomenon impaired in patients with the following predisposing conditions: stroke, diabetes mellitus (DM), leprosy and elderly. A transversal study was maded with a quantitative approach, realized at four followings institutions in Fortaleza/CE: stroke unit of a tertiary hospital, specialized dermatology center, integrated care center to the DM and a community center for the elderly. The sample consisted of 365 participants. The collection instrument, adapted from Morais (2013) study contains sociodemographic variables on lifestyle, clinics and evaluation of the tactile sensory modalities. The tested areas were face, hands and feet. Data were collected by primary source, with interview and physical examination, and secondary source by hospital records between October 2014 and August 2015. Statistical analysis was performed with the support of IBM SPSS software, version 21.0 for Windows and the R version 2.12.1 software. To check the sensitivity and specificity of tactile modalities was used latent class analysis model. The study was approved in three Committees of Ethics in Research. 42 of the participants had strokes, 122 DM, 104 leprosy and 97 aged. Of these 60% were female, mean 51.12 (±15.3) years of age, coming from Fortaleza (66.8%), living with a partner (52.9%). With regard to education was identified average of 9.42 (±5.22) years of study and monthly family income of 1986.63 (±1933.55) reais. As to life habits, 69.9% were not smokers, 86.3% did not consume alcoholic beverages and 58.1% did not practice physical activity. Most respondents was independent of the basic activities (70.7%) and instrumental (84.2%) of daily life. In the analysis of the final model of latent class for all participants, considering all the tactile sensory modalities, Change in the perception of texture, change in stereognosis and Extinguishing a touch simultaneously were specific. While tactile sensory modalities Change in perception of light touch, change in perception of pressure, change in perception of tactile location, impaired somatosensory discrimination and change in perception of temperature were sensitive to phenomenon. The phenomenon was present in 32.55% of the participants surveyed in the study. It is concluded that the phenomenon impaired tactile sensory perception were present in the four investigated conditions, which compromises the resumption of daily activities after the acute event of the ischemic stroke and increases the risks of imbalances and falls in all groups.